Technical and environmental performance assessment of the Iranian power plants: a semi-disposal DEA approach - Mokari, Masod; Ghiyasi, Mojtaba; Emami Meybodi, Ali (Journal of Environmental Engineering and Landscape Management, 2022)
One of the most important issues is to achieve maximum production of energy from a particular energy source, which ensures the complete protection of the environment. The current paper as the first application of flexible and powerful semi-disposability approach, performs an empirical technical and environmental efficiency analysis for 39 natural gas and gasoline power plants, including governmental and private property, during the years 2011–2016. Different scenarios for environmental analysis, namely, weak disposability, strong disposability and semi-disposability with different returns to scale assumptions are performed in the analysis. The primary results of multivariate assessment based on constant returns to the scale shows that 7 power plants with state ownership and 8 power plants with private ownership were among the most efficient power plants from the technical-environmental perspective. Parametric and non-parametric tests are performed and the result shows better performance of private power plants compared with governmental power plants.